INFECTION RATES OF BOVINE TRYPANOSOMOSIS IN SOME AREAS OF SUDAN - Nadia, M Osman, Nadia; M E, ElSagdi,; I. A , Mohammed,; A, I; A. H, A/Rahman (Journal of Veterinary Medicine and Animal Production, 2022)
A survey on bovine trypanosomosis was conducted in different areas of Sudan including Khartoum (Khartoum state), Nyala (South Darfur State), Obeid (North Kordofan state), Gedaref (Gedaref state), Wad Madani (Gazira state), Unity and Blue Nile States. Trypanosomes infections were found in all the seven states surveyed. Out of 1852 cattle, 156 were infected with various species of trypanosomes (105 in Blue Nile and 51 in the other states), with the total infection rate of 8.42%. In the different areas surveyed except the Blue Nile state the lowest infection rate (0.42%) was recorded in Wad Madani while the highest (28.57%) was recorded in Nyala with a significant (P˂0.05) difference. In these areas, the most common trypanosome species detected were T. vivax (72.7%) followed by T. theileri (27.3%). The infected animals had PCV range of 20.3%-32.7% with a mean of 26.63%, while uninfected animals had PCV range of 26.25%-33.1% with a mean of 28.49 %. In Blue Nile area, the lowest infection rate (0%) was recorded in April, 2009 while the highest 43.3% was in June 2010. The most common trypanosome species in Blue Nile were T. vivax (71.4%) followed by T. congolense (25.71%). The prevalence of T. vivax was significantly (P˂0.05) higher than the other trypanosome species. T theileri (2.86%) was, also reported in December 2008, while T. brucei infection was not found. Infected animals had PCV range of 18.5%-25% with a mean average of 22.8%, while in uninfected animals the range was 20.2%-33.34% with a mean average of 25.5%, with no significant difference between infected and uninfected cattle.